The Impact of Empowering Leadership on Preschool Teachers’ Job Well-Being in the Context of COVID-19: A Perspective Based on Job Demands-Resources Model - Nong, Liying; Ye, Jian-Hong; Hong, Jon-Chao (Frontiers in Psychology, 2022)
The COVID-19 epidemic in the early 2020s is making a big difference for educators around the world. For the past 2 years, the curriculum and working patterns have been overturned in response to this epidemic, which has brought unprecedented challenges and physical and mental stress to preschool teachers. This situation can have a drastic impact on the acquisition of job well-being for preschool teachers. During this special time, the leader’s management style will also influence the psychological feelings of the organization’s staff. For example, empowering leadership is an important management function that empowers subordinates, emphasizes the meaning of work, promotes participation in decision-making, and expresses confidence. Therefore, in the current COVID-19 pandemic context, it is worthwhile to explore the topic of empowering leadership to ensure preschool teachers’ well-being, by balancing work demands and work resources in a way that facilitates a sense of organizational support and reduces job stress, while relatively fewer studies have been conducted on the relationship between preschool teachers’ job well-being in the context of the COVID-19 pandemic. Based on this, this study proposed a research model from the theoretical perspective of the Job Demands-Resources Model to explore the influence of empowering leadership, sense of organizational support, and job stress on preschool teachers’ job well-being in the context of the COVID-19 pandemic. To achieve the purpose of this study, a convenience sampling method was used to invite 500 preschool teachers in China to complete a questionnaire survey, and after removing invalid samples and data with incomplete answers, reliability and validity analyses and model fit tests were conducted, followed by a structural equation modeling method for path analysis. The results of the study showed that (1) in the kindergarten work context, empowering leadership showed a significant negative effect on job stress, but a significant positive effect on job well-being and a significant positive effect on sense of organizational support. (2) Sense of organizational support had a significant negative effect on job stress but a significant positive effect on preschool teachers’ job well-being. (3) Preschool teachers’ job stress and job well-being showed a significant negative effect. The contribution of this study was to explore the relationship between understanding leadership empowerment and preschool teachers’ job well-being in the context of the COVID-19 pandemic based on the Job Demands-Resources Model, which will facilitate educational organizational contexts to empower preschool teachers to work harder to reduce their job stress as well as enhance their sense of organizational support and promote the acquisition of job well-being.